An Analysis of Management Students’ Perceptions toward the Use of AhaSlides as an Instructional Medium in the Presentation in English Course at a University in Sumenep - Lailiy Kurnia Ilahi; Wahyudi Wahyudi; Supriadi Supriadi; Laily Fajariyah; Endang Agus Sulasmi; Budyi Suswanto (PT. Intelek Cendikiawan Nusantara, 2026)
The rapid development of technology has encouraged the use of digital platforms as instructional media in higher education. Educators are expected to apply learning tools that can increase students’ motivation, engagement, and understanding. AhaSlides is an interactive platform that provides features such as presentations, audio, visual, and audiovisual elements to support more dynamic learning activities. This study aimed to analyze students’ perceptions of the use of AhaSlides as an instructional medium in the Presentation in English course. The research employed a descriptive quantitative method. The participants were fourth-semester Management students at a university in Sumenep. Data were collected through a questionnaire consisting of eleven statements, including five statements measuring students’ perceptions before using AhaSlides and six statements measuring their perceptions after its implementation. The results showed that students’ perceptions before using AhaSlides were categorized as very poor, indicating low motivation and ineffective learning experiences. However, after the implementation of AhaSlides, students’ perceptions improved significantly and were categorized as very good. This finding indicates that AhaSlides effectively enhances students’ engagement, motivation, and understanding of Presentation materials. Therefore, AhaSlides can be considered an effective instructional medium to improve the quality of teaching and learning in the Presentation in English course